Why Industry Propaganda and Political Interference Cannot Disguise the Inevitable Role Played by Human Exposure to Aluminum in Neurodegenerative Diseases, Including Alzheimer’s Disease - Exley, Christopher (Frontiers in Neurology, 2014)
In the aluminum age, it is clearly unpalatable for aluminum, the globe’s most successful metal, to be implicated in human disease. It is unpalatable because for approximately 100 years human beings have reaped the rewards of the most abundant metal of the Earth’s crust without seriously considering the potential consequences for human health. The aluminum industry is a pillar of the developed and developing world and irrespective of the tyranny of human exposure to aluminum it cannot be challenged without significant consequences for businesses, economies, and governments. However, no matter how deep the dependency or unthinkable the withdrawal, science continues to document, if not too slowly, a burgeoning body burden of aluminum in human beings. Herein, I will make the case that it is inevitable both today and in the future that an individual’s exposure to aluminum is impacting upon their health and is already contributing to, if not causing, chronic diseases such as Alzheimer’s disease. This is the logical, if uncomfortable, consequence of living in the aluminum age.